“Insomniac Story” Penciptaan Game Berbasis Cerita - Emanuel Trisnajati; Arif Sulistiyono (Journal of Animation and Games Studies, 2018)
Story-based game "Insomniac Story" is a horror-themed game with the story-based point-and-click adventure genre. This game tells of a girl named Amanda who got a bad experience when she was left at home alone by her parents for several days. Amanda's bad experience was the presence of someone who lurked Amanda at her home.This game raises elements in psychology as a basic concept in the story. The main part of psychology raised in this game is the area related to mental illness that causes disruption of perception of reality. The story in the game doesn't tell clearly whether the mysterious person who terrorized Amanda is real or just hallucinates, and these two possibilities can be accepted as reasonable explanations. Game is one form of delivery media that exists. This "Insomniac Story" game was made with the intention of conveying stories in interesting forms. This game has a playtime of around 10-15 minutes. Horror themes are needed to share supporting aspects in order to show the storyline. Keywords: Game, Story Based, 2D Point-and-Click, Adventure, Horror